Corporate brand identity in higher education: a relational perspective - Barros, Teresa (2013)
Identity is traditionally defined as an emission concept (Kapferer, 2008). Yet, some research points out that there are external factors that that can influence it (Kennedy, 1975; Markwick e Fill, 1997; Balmer e Gray, 2000). This subject is even more interesting if one considers corporate brands. According to Aaker (2004) the number, the power and the credibility of corporate associations are bigger in the case corporate brands. Literature recognizes the influence of relationships between companies in identity management (Hakansson and Snehota, 1989, 1995; Hakansson and Ford, 2002). Yet, given the increasingly important role of corporate brands, it is surprising that to date no attempt to evaluate that influence has been made in corporate brand´s identity management and reputation. Also Keller and Lehman (2006) highlight relationships and costumer experience as two areas requiring more investigation. The authors argue that corporate brand´s identity can be developed under a relational perspective using relationships with other recognised brands in order to generate positive reputations in stakeholders. Based in relationship and corporate brand identity management, a framework is developed to identify how corporate brands select, develop and invest in relationships with other brands. The context of the proposed relationship concept is the services area (Dwyer et al, 1987; Moorman et al, 1992; Rauyruen et al, 2005 and Hennig-Thurau and Klee, 1997). An empirical qualitative research is designed using two reputational technological higher education institutions (two corporate brands) acting in Portuguese public higher education market.